Meaningful Economics: An Islamic Perspective On Human Well-Being and Ethical Value - Ayif Fathurrahman; Muhammad Danish Farhad Bin Zainol Asri (IECON: International Economics and Business Conference, 2025)
This article analyzes the crisis faced by several multinational corporations, in light of the growing ethical awareness among Muslim consumers regarding global issues such as the Israeli aggression in Gaza. Employing a qualitative-descriptive approach and literature review, this study examines how the phenomenon of consumer boycotts reflects a paradigm shift in the consumption behavior of Muslim societies. The findings reveal that such boycotts are not merely rooted in political sentiment but also represent an expression of the values embedded in maqāṣid al-sharī‘ah, including justice, solidarity, and moral responsibility. Furthermore, the article proposes the framework of meaningful economics as an alternative to the conventional economic model, which often tends to be reductionist and unresponsive to evolving social dynamics. Within the Islamic economic paradigm, consumption and production are regarded as meaningful activities that encompass both spiritual and ethical dimensions. This study recommends that global corporations adopt value-based business models and remain attentive to the moral sensitivities of Muslim consumers as a long-term sustainability strategy.